2017
DOI: 10.1200/po.17.00182
|View full text |Cite
|
Sign up to set email alerts
|

Decision-Making Preferences About Secondary Germline Findings That Arise From Tumor Genomic Profiling Among Patients With Advanced Cancers

Abstract: Purpose In patients with advanced cancers, tumor genomic profiling (TGP) can reveal secondary germline findings (SGFs) with regard to inherited disease risks. This study examined the process by which patients with advanced cancers would decide about whether to learn these SGFs and their preferences about specific challenging decision scenarios, including whether patients should be required to receive SGFs and whether SGFs should be returned to the family after a patient’s death. Patients and Methods We conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…A meta-analysis of BRCA1/2 mutation carriers and noncarriers summarized that women who were mutation carriers experienced higher emotional distress immediately after receiving results, which decreased to pretesting levels with time (Hamilton et al, 2009), highlighting the complex interplay between the impact of cancer and receipt of genetic and genomic tests on one's emotional state. In our earlier work we found that despite the possibility of genomic testing increasing psychosocial concerns particularly when receiving unwanted knowledge, the majority of advanced cancer patients were interested in receiving results, especially if they were actionable (Best et al, 2020), which is supported by other studies (Hamilton et al, 2017). Concurrently, we also found that patients had heightened optimism and hope that the result would be actionable and that a drug would be readily available and successful for their cancer, despite being informed that the likelihood of receiving an actionable result following CGP was low (Best et al, 2019).…”
supporting
confidence: 66%
“…A meta-analysis of BRCA1/2 mutation carriers and noncarriers summarized that women who were mutation carriers experienced higher emotional distress immediately after receiving results, which decreased to pretesting levels with time (Hamilton et al, 2009), highlighting the complex interplay between the impact of cancer and receipt of genetic and genomic tests on one's emotional state. In our earlier work we found that despite the possibility of genomic testing increasing psychosocial concerns particularly when receiving unwanted knowledge, the majority of advanced cancer patients were interested in receiving results, especially if they were actionable (Best et al, 2020), which is supported by other studies (Hamilton et al, 2017). Concurrently, we also found that patients had heightened optimism and hope that the result would be actionable and that a drug would be readily available and successful for their cancer, despite being informed that the likelihood of receiving an actionable result following CGP was low (Best et al, 2019).…”
supporting
confidence: 66%
“…Without such recommendations, one-third of patients with endometrial cancer and all patients with cervical cancer whose tumor sequencing results met ESMO guidelines were not referred for germline testing. Lack of referral for genetic testing is important as research indicates that patients are interested in learning their germline status and desire guidance from oncologists; without provider recommendations, patients are less likely to proceed with genetic counseling and testing 15 16. In this study, only 26.8% of those receiving germline testing underwent testing as a result of tumor sequencing.…”
Section: Discussionmentioning
confidence: 80%
“…Research supports that patients desire guidance from their oncologists; without specific recommendations from their providers, patients are less likely to proceed with genetic counseling and testing. 21 Given competing demands of oncologists’ time related to ongoing cancer therapy and symptom management, simplifying the process by which patients become aware of the possibility of germline findings arising from TGP and have access to germline confirmation is critical. To address this knowledge gap, we are developing a TGP fact sheet for patients and providers to provide anticipatory guidance regarding potential germline findings.…”
Section: Discussionmentioning
confidence: 99%